Patogenesis of White Spot Virus Infection (WSV) on Black Tiger Shrimp (Penaeus Monodon Fab.) - Alifuddin, M.; Dana, D.; Eidman, M.; Malole, M.B.; Pasaribu, F.H. (Jurnal Akuakultur Indonesia, 2003)
The pathogenesis determination of white spot disease on tiger shrimp to study effect of various white spot virus concentrations on pathological changes was conducted by water borne infection with the several of viral concentration within 60 minute using black tiger shrimp post larvae. The result showed the incubation period of the disease based on appeareance of white spot at 2-2000 ng/ml is 17 days p.i., whilst at 0.2-0.02 ng/ml is 19 days p.i. It seem, the lowest viral concentration stimulated respond immune of shrimp which indicated by low mortalities percentage (13.3 and 10.6%). Stage of disease development recognized throughout histological analyse, based on hypertropie of nuclei, is stage 0-4. Based on microscopic observation, the white spot seen pleomorphic forms which related to its development and seem to be used as rapid diagnostic tool for indicating of WS infection. This study also proved by histological observation that hepatopancreatic tissue can be infected as well as epidermis of carapace, gill, intestine and lymphoid tissues. One of pathological changes by WS infection is white spot as pathogonomic lesi of the disease. Keyword : White spot virus, infectious disease, tiger shrimp (Penaeus monodon Fab.)